2021
DOI: 10.3390/molecules26020422
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin Derivatives in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a non-communicable disease characterized by a chronic inflammatory process of the gut and categorized into Crohn’s disease and ulcerative colitis, both currently without definitive pharmacological treatment and cure. The unclear etiology of IBD is a limiting factor for the development of new drugs and explains the high frequency of refractory patients to current drugs, which are also related to various adverse effects, mainly after long-term use. Dissatisfaction with current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 107 publications
1
46
0
1
Order By: Relevance
“…Coinciding with the results of the present work, Chen et al [36] reported that administration of coumarins, including fraxetin and isofraxidin, was associated with significant decrease in NLRP3 inflammasome at the gene expression level. Di Stasi [37] attributed this decrease to the ability of fraxetin to inhibit the main initiators of activation of NLRP3 inflammasome including danger-associated and pathogen-associated molecular patterns. In addition, the ability of fraxetin to inhibit NF-κB expression may have a regulatory role on NLRP3 inflammasome production and activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Coinciding with the results of the present work, Chen et al [36] reported that administration of coumarins, including fraxetin and isofraxidin, was associated with significant decrease in NLRP3 inflammasome at the gene expression level. Di Stasi [37] attributed this decrease to the ability of fraxetin to inhibit the main initiators of activation of NLRP3 inflammasome including danger-associated and pathogen-associated molecular patterns. In addition, the ability of fraxetin to inhibit NF-κB expression may have a regulatory role on NLRP3 inflammasome production and activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…The structure determination of these coumarins were elucidated based on their spectroscopic properties as well as of their chemical evidence. A variety of pharmacological activities have been reported for coumarins and their analogs, including anticoagulant, anticancer, antioxidant, antiviral, antidiabetic, anti-inflammatory, antibacterial, antifungal, antileishmanial, and antineurodegenerative activities [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Our studies on the bioactive constituents from medicinal plants, such as Angelica furcijuga Kitagawa [ 14 , 15 , 16 , 17 ] and Mammea siamensis (Miq.)…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease is regarded as a non‐communicable disease lacking effective pharmacological therapy 27 . In the current study, we sought to determine the regulatory mechanism of miR‐378a‐3p‐containing MSCs‐EVs in IBD and identified that it could inhibit the progression of IBD by blockade of the AQP4/GATA2/PPAR‐α axis.…”
Section: Discussionmentioning
confidence: 99%